HARUN NASUTION (Islam Rasional dalam Gagasan dan Pemikiran) - Nurhadi, M.HI (EDUKASI: Jurnal Pendidikan Islam, 2013)
Islam is a logical religion. Consequently, those who cannot think logically cannot be categorized as those who poseses a religion. A logical religion is one that has rational or logical teachings. This also means that those who believe in such a religion will not become a blind following taqlid, this is even worse if the followed only one or certain madzhab or school.